Determination of Pipe Diameter Using Optimization Method - Pavlov Mikhail Vasilyevich; Vafaeva Khristina Maksudovna; Karpov Denis Fedorovich; Bhatnagar Sanjay; Kommanaboina Uma Shankar; Sharma Dikshit; Singh Digvijay; Sateesh N.; Singh Pankaj Kumar (E3S Web of Conferences)
During the design phase of engineering networks, a critical issue remains the selection of pipe diameters that minimize capital investments for transporting the heat carrier from the heat source to the consumers. Object of study: a pressurized pipeline of circular cross-section with a moving heat carrier. Subject of study: total monetary costs for transporting the heat carrier as a function of the chosen pipeline diameter. Objective of study: to determine the pipe diameter that achieves maximum cost savings for transporting the heat carrier under given design conditions. Research methods: theory of hydraulic calculation for circular cross-section pipelines and theory of heat transfer through a single-layer cylindrical wall under steady-state conditions. Research results: using an example from a centralized heating system pipeline section, it was established that for a mass flow rate of the heat carrier equal to 32.9 t/h, the optimal pipe size would be 76×3 mm (nominal diameter 70 mm). Under current tariffs for thermal energy (24.82 USD/Gcal) and electrical energy (6.65 USD/(MW⋅h)), the total monetary costs for transporting the heat carrier over a heating season would be 56.28 USD per 1 running meter of pipeline. In comparison, with a nominal diameter of 50 mm, the total costs amounted to 90.37 USD; with a diameter of 80 mm, the costs were 63.29 USD. The developed method for hydraulic design calculations is universal and can be applied in the design of engineering networks where the working medium is a moving heat carrier (steam or hot water).